Marketing Strategy for Private Elementary Schools in The City of North Sumatra in Increasing the Number of Students - Dwi Fany Fransiska Dewi Butar Butar (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This study aims to determine the marketing strategy carried out at Teladan Private Elementary Schools in North Sumatra to increase the number of students. This type of research is qualitative research. Data collection techniques are observation, interviews and documentation. The results of research conducted at Exemplary Private Elementary Schools in North Sumatra are that the marketing strategy used by increasing the number of students is to use the 7P marketing mix, namely, Product, Price, Place, Promotion, People, Physical Evidence and Process. The next marketing strategy is to create and implement the PSB (New Student Acceptance) program. The results of the study show that the marketing strategy to increase the number of new students is to form a committee directing the program to be implemented by targeting each teacher to carry out a promotion so that students register.